Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Altona Rare Earths soars as it enters MoU to acquire rare earths project (Vox Markets, 2021)
Shares in Altona Rare Earths soared by over 60% today following the news that the group has entered into an MoU to acquire up to 70% in the Monte Muambe Rare Earths Project. Should it choose to proceed with the investment following a 90-day due diligence period, the project would represent its first venture into a carbonatite hosted REE asset.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência